Job Satisfaction Factor Affecting the Intention to Stay with the Organization of the Special Training Division, Border Patrol Police - Chalongpoom, Huttaya; Nikornpttaya, Saowaluk; Ingun, Rungsun (Journal of Graduate MCU KhonKaen Campus, 2023)
The objectives of this research were 1) to study the job satisfaction factor affecting the intention to stay with the organization of the Special Training Division, Border Patrol Police; (2) to study the level of the intention to stay with the organization of the Special Training Division, Border Patrol Police; (3) to study the relationship between job satisfaction factor and the intention to stay with the organization of the Special Training Division, Border Patrol Police; and (4) to study the guidelines for developing the level of inten intention to stay with the organization of the Special Training Division, Border Patrol Police. This study was mixed-method research. The sample group used in the quantitative research was non-commissioned police officers, totals of 306 people, which was calculated using the formula of Taro Yamane (1973 : 727). The research instrument was the 5 point rating scale questionnaire based on the criteria of Likert‘s Scale. The questionnaire had reliability value of 0.872. For the qualitative key informant groups, were 2 groups, including the non-commissioned police officer who had requested for relocation, and who were appointed to relocate outside of the precinct, totals of 6 people. The results found that 1) the overall of job satisfaction factor was at high level, when classified by aspects using the arithmetic means in descending order, can be sorted as follows: Colleague; Job description; Opportunity for career advancement; Command; and Revenue 2) the overall level of intention to stay with the organization was at high level 3) the job satisfaction factor had positively correlated with the level of intention with the organization under the Special Training Division, Border Patrol Police, in low level (r=0.395), with a statistically significant at .01 level. 4) Most police officers agree that The police have to do their job of repression and investigation because of the challenges. and has an impact on Thai society more than any other work